(untitled) (Journal of Economic Research & Business Administration, 2016)
In modern society, from year to year increasing the role of universities in the promoting of country image and socio-economic development. In order to improve the competitiveness of education in the advanced countries used different methodologies and criteria to identify key world class leading organizations. This article provides an overview of the international rankings, as well as it is importance for improving the competitiveness of higher education institutions. The using of the article data and analysis may help to transform the scientific and educational potential of national universities in the country and developing world-class research universities. In the future it is expected to conduct a comprehensive analytical study to identify factors affecting the competitiveness of the Kazakhstani universities. And to develop the methodology for selection of universities; establish the scientific and methodological basis for the promotion of higher education institutions on international level.